PHYSIOLOGICAL FEATURES AND ANALYSIS OF SALVIA OFFICINALIS L. IN THE BOTANICAL GARDEN OF THE NATIONAL UNIVERSITY OF UZBEKISTAN - G. Sh. Ergasheva (Galaxy International Interdisciplinary Research Journal, 2021)
Salvia officinalis L. is a shrub belonging to the family of mint.